Impact of Boycott, Divestment, and Sanctions Movement on Indonesia’s Economy - Gina Hikmatul Ula; Nurul Hikmah; Rochanda Wiradinata; Nurul Senja (Greenation Research & Yayasan Global Resarch National, 2024)
Product boycott refers to not using and purchasing a product from a particular organization or company. The goal is to pressure Israel to fulfill what the Boycott Divestment and Sanctions (BDS) movement describes as Israel's obligations under international law, defined as withdrawal from the occupied territories, removal of the separation wall in the West Bank, full equality for Arab citizens-Palestinians in Israel, and respect, protect and advance the rights of Palestinian refugees to return to their homes and property. This research uses qualitative methods with literature studies. Meanwhile, the approach applied uses qualitative descriptive analysis with data related to the problem in the study. Writers use reading sources such as journals, articles, news, etc. as writing material and then conclude. The boycott of foreign products, especially Israeli products in Indonesia, has a positive impact on the growth of domestic product revenues. However, the boycott movement reduces economic growth because it reduces demand and increases the number of unemployed. The estimation method used in this research presents certain advances compared to other methods found in the literature because it makes it possible to determine the impact of the BDS movement on the Indonesian economy while still considering the interdependence between different sectors, as well as able to decide on its implications fairly compared to other industries. This research also uses large amounts of data, so it is hoped that it can increase the strength of the research conclusions